GROSS MOTOR SKILL LEVELS IN PRESCHOOLERS - Supriady, Andy (STKIP Muhammadiyah Kuningan, 2024)
The purpose of this study was to determine the level of gross motor skills in preschool children. The participants in this study were preschool children, with a total of 30 children aged 5-6 years, who were selected by convenience sampling technique. The instrument of this study was the Test of Gross Motor Development-2 (TGMD-2). This study is a descriptive analysis. The results of gross motor skills showed that 5 children were in the below average assessment category (17%), 7 children were in the very poor assessment category (23%), and 18 children were in the poor assessment category (60%). Therefore, the majority of the total children's gross motor data is in the poor category. In conclusion, the competence of preschool children's gross motor skills needs to be improved by optimizing the teaching-learning process. This study contributes to the implementation of further research, namely the need for treatment to optimize Gross Motor skills in preschool children. The urgency to conduct appropriate and measurable treatments to improve preschool children's gross motor skills is important to be considered in the learning and teaching process.